Image and coding techniques - Issa, Sinzobakwira; Khalifa, Othman Omran (IIUM Press, 2011)

(untitled)
The visual communication has reached a point of becoming a lively area in this new era. The main challenge for implementing video communication system is accessible bandwidth of the network. Usually this necessary bandwidth is not enough for the deployment of enormous amount of video data